Psychology capital and organizational commitment of novice police: the mediation effect of career adaptability - Sutrisno, Aristianto Budi; Suhariadi, Fendy; Wijoyo, Suparto; Aldhi, Ian Firstian; Teofilus, Teofilus; Hardaningtyas, Dwi (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research aims to provide an understanding of the mechanisms underlying organizational commitment (OC) by utilizing psychological capital (PsyCap) as an antecedent and career adaptability (CA) as a mediator in this relationship. This study employs the conservation of resources (COR) theory to elucidate how PsyCap and CA can assist organizational members in enhancing OC when assessing the workforce quality in police settings. The study was conducted at police academy and state police school in Indonesia. The sampling technique adopted purposive sampling, targeting novice police totaling 417 individuals. Concerning the relationship between PsyCap and CA denoting a statistically significant positive relationship. This indicates that as PsyCap increases, CA tends to rise as well. The results demonstrate that the relationship between PsyCap and OC is not statistically significant. The relationship between CA and OC indicates an extremely significant positive relationship, meaning that a higher CA leads to an elevated OC. The indirect relationship between PsyCap and OC, when considering the mediating effect of CA on the relationship between PsyCap and OC, implies that PsyCap has a significant positive influence on OC through CA. It can be concluded that CA fully mediates the relationship between PsyCap and OC.